AN ASSESSMENT OF THE SPATIAL RELATIVITY OF HEALTH, LITERACY AND SOCIO-ECONOMIC GROWTH INDEX USING GIS TECHNIQUES: A CASE STUDY ON UDUPI SOUTH - Maddodi, B S; Udayashankara, H N; Raghavan, B R; Mathews, Alina E (European Scientific Journal, ESJ, 2013)
GIS can be thought of as a system that digitally creates and "manipulates" spatial areas that may be jurisdictional, purpose or application-oriented for which a specific GIS is developed. Therefore, in a general sense, the term describes any information system that integrates, stores, edits, analyzes, shares and displays geographic information for informing decision making. GIS applications are tools that allow users to create interactive queries (user-created searches), analyze spatial information, edit data, maps, and present the results of all these operations. In the simplest terms, GIS is the merging of cartography, statistical analysis, and database technology. This paper presents the results of using GIS as a tool to study the health status of Udupi District. Health is a parameter that is influenced by various factors both environmental and non-environmental. The thesis, at the latter stage, emphasizes the influence of non-environmental factors such as literacy and socioeconomic index on health status of Udupi district. The results demonstrate an affirmative relation of health status with health literacy, awareness and socio-economic index of a locality, despite the well-knit health care facilities available within the district.